A Proposal to Apply SignWriting in IMSC1 Standard for the Next-Generation of Brazilian DTV Broadcasting System - Lobeiro, Marcelo; Vaz, Rodrigo Admir; Alves, Luiz Gustavo Pacola (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2022: Proceedings of the 28th Brazilian Symposium on Multimedia and the Web, 2022)
This paper aims to introduce the possibility of using SignWriting - a writing system that describes movements in sign language - together with IMSC1 (Internet Media Subtitles and Captions) to provide an accessibility feature for hearing-impaired users in next generation Brazilian DTT (Digital Terrestrial Television system (named TV 3.0). IMSC1 standard has two profiles that are intended for subtitle and caption delivery worldwide: text- and graphic-only. SignWriting uses statically written visual symbols to represent dynamic movements in sign language, exactly as subtitle and caption. In this scenario, TV 3.0 can take advantage of IMSC1 to deliver SignWriting information by translating from text or from audio, as closed caption does nowadays. The objective of this paper is to use IMSC1, which has been adopted by TV 3.0, to apply SignWriting and consequently to improve user accessibility.